Otoliths of marine fishes record evidence of low oxygen, temperature and pH conditions of deep Oxygen Minimum Zones - Cavole, Leticia Maria; Limburg, Karin E.; Gallo, Natalya D.; Gro Vea Salvanes, Anne; Ramírez-Valdez, Arturo; Levin, Lisa A.; Aburto-Oropeza, Octavio; Hertwig, Andreas; Liu, Ming-Chang; McKeegan, Kevin D. (Deep-sea research. Part 1, Oceanographic research papers, 2023)
The deep-sea is rapidly losing oxygen, with profound implications for marine organisms. Within Eastern Boundary Upwelling Systems, such as the California and the Benguela Current Ecosystems, an important question is how the ongoing expansion, intensification and shoaling of Oxygen Minimum Zones (OMZs) will affect deep-sea fishes throughout their lifetimes. One of the first steps to filling this knowledge gap is through the development of tools and techniques to track fishes’ exposure to hypoxic (<45 μmol kg-1), low-temperature (∼4-10°C) and low-pH (∼7.5) waters when inhabiting OMZs. Here, we examine if the otoliths of deep-sea fishes living in OMZs exhibit distinct patterns of elemental and isotopic composition, which could be used to monitor their exposure history to severely hypoxic and low-pH waters. We hypothesize that the unique biogeochemistry of OMZs (i.e., low-oxygen, low-pH, and the presence of dissolved elements) will impart unique elemental and isotopic signatures upon the otoliths of both long-lived and short-lived deep-sea fishes living within it. We analyzed the otoliths of six deep-sea fish species from three OMZ regions: the Southern California Bight and the Gulf of California in the Northeast Pacific Ocean, and the Namibian shelf in the Southeast Atlantic Ocean. Three complementary techniques were applied: laser ablation inductively coupled plasma mass spectrometry, secondary ion mass spectrometry and scanning X-ray fluorescence microscopy. We observed that deep-water OMZ-dwelling fishes spanning a range of life-history traits (e.g., longevity, maximum size, growth rate, parental investment and thermal history inferred by δ18O) exhibited a common elemental fingerprint (with respect to Sr:Ca, Mn:Ca, Ba:Ca, Cu:Ca and Mg:Ca) when compared to a shallow-water marine fish from better-oxygenated waters. Our findings suggest that the underlying mechanism for the common elemental fingerprinting of otoliths of OMZ-dwelling fishes is attributed to the unique biogeochemistry found on the margins of these highly productive upwelling systems as well as the physiological constraints resident organisms are perennially exposed to, including low oxygen, pH and temperature conditions.
Online veröffentlicht: 2. Dezember 2022
Gesehen am 24.06.2023